Local forest management: conclusion - Edmunds, D.; Wollenberg, Eva Karoline; Contreras, A.P.; Liu Dachang; Kelkar, G.; Nathan, D.; Sarin, M.; Singh, N.M. (Routledge, 2003)
This chapter concludes from a study of the impacts of forest devolution policies in China, India and the Philippines that devolution has had significant impacts, but mostly on increasing forest cover. Changes in livelihoods were mixed, and control over forests was little changed. In some cases, de facto control and benefits actually decreased. Forest departments are ill-suited to leading economic development among forest users, as their interests are too divergent. Other state agencies and third party facilitators are necessary. It concludes with a set of recommendations for improving policy support to local forest management.